PERTUMBUHAN DAN HASIL CABAI BESAR AKIBAT PEMBERIAN LUMPUR LAUT CAIR DAN PUPUK KANDANG KAMBING PADA TANAH GAMBUT - Tatang Abdurrahman (Jurnal Agroekoteknologi, 2018)
The research was to find out liquid coastal sediment and goat manure effects of growth and yield chili on peat soil were conducted at the experimental farm of the Faculty of Agriculture University Tanjungpura Pontianak, from March until June 2018. The research was arranged in Randomized Completely Design with two factors and each treatment combination was replicated three times. The first factor was liquid coastal sediment dosages (0; 0,5; 1; 1,5 L plant-1), while second factor was goat manure dosages (0; 50; 100; 150 g plant-1).The result of first experiment showed that there was no interaction between the liquid coastal sediment and goat manure in influencing plant height, plant dry weight, number of fruit crops, weight chili crops and the weight of fruit crop. The application of liquid coastal sediment material significantly improved the plant height, plant dry weight, number of fruit crops, weight chili crops and the weight of fruit crop, while the application of goat manure significantly improved the plant height, plant dry weight and the weight of fruit crop. The application of liquid coastal sediment 1 L plant-1 and goat manure 100 g plant-1 could promote the growth and yield of soybean in peat soil.